Disruption of HPV16-E7 by CRISPR/Cas System Induces Apoptosis and Growth Inhibition in HPV16 Positive Human Cervical Cancer Cells. (20th July 2014) - Hu, Zheng; Yu, Lan; Zhu, Da; Ding, Wencheng; Wang, Xiaoli; Zhang, Changlin; Wang, Liming; Jiang, Xiaohui; Shen, Hui; He, Dan; Li, Kezhen; Xi, Ling; et al.
Abstract : High-risk human papillomavirus (HR-HPV) has been recognized as a major causative agent for cervical cancer. Upon HPV infection, early genes E6 and E7 play important roles in maintaining malignant phenotype of cervical cancer cells. By using clustered regularly interspaced short palindromic repeats- (CRISPR-) associated protein system (CRISPR/Cas system), a widely used genome editing tool in many organisms, to target HPV16-E7 DNA in HPV positive cell lines, we showed for the first time that the HPV16-E7 single-guide RNA (sgRNA) guided CRISPR/Cas system could disrupt HPV16-E7 DNA at specific sites, inducing apoptosis and growth inhibition in HPV positive SiHa and Caski cells, but not in HPV negative C33A and HEK293 cells. Moreover, disruption of E7 DNA directly leads to downregulation of E7 protein and upregulation of tumor suppressor protein pRb. Therefore, our results suggest that HPV16-E7 gRNA guided CRISPR/Cas system might be used as a therapeutic strategy for the treatment of cervical cancer.